METHODS PRE-TREATMENT OF CORN SEED IN THE ELECTROMAGNETIC FIELD - Chmil, A.; Lazariuk, K. (Energy and Automation, 2016)
The analysis methods of pre-treatment of cereal seeds to enhance germination and crop yields. The most promising methods of pre-treatment of seeds.